التزام الطبيب بتبصير المريض (Al-Farooq Journal of Sciences, 2026)
The doctor-patient relationship, and the doctors commitment to informing the patient of the proposed treatment , are among the most important factors that contribute to maintaining trust in this relationship .    This study is important because it demonstrates how the Libyan legislator deals with the obligation to inform the patient and the extent to which adequate protection is provided for the patient .